Karakteristik Amplifier Class D Menggunakan Field Effect Transistor (FET)Type IRF9530 Dan IRF630 - Budi Santoso; Zainal Abidin (Universitas Islam Lamongan, 2020)
In the development of power amplifiers, MOSFETs are widely used in the composition of the manufacture. As is known, MOSFETs have a longer on-off time loss compared to IGBT. The loss on the on-off time has an impact on the heat generated by the MOSFET. Class D Audio Amplifier is basically a Switching-Amplifier or Pulse Width Modulation-Amplifier. High efficiency means that it will produce low power dissipation, thus the power wasted is relatively lower when compared to class A, B or AB amplifiers. Because the class D audio amplifier can be said to be more economical because it does not require a large heatsink and a large power supply. The manufacture of the Class D power amplifier system uses a voltage of 28.5 volts DC on the final transistor IRF9530 AND IRF630 measuring the input transistors of 3.3 volts DC, 28.5 volts DC. In the test using an oscilloscope type LS 8050, 50 MHz frequency, the position of the audio input off of the amplifier has sound defects. Testing of the power amplifier is carried out when the treble on the input tone control is full db in the defective amplifier wave.